Application of personal mastery and leadership in learning organizations - Shahmandi, Elham; Shahhosseini, Mohamad; Basri, Ramli (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
The purpose of this research was to investigate the correlation between transformational .and transactional leadership styles of Iranian high school principals with the application of learning organization indices (personal mastery, mental model, shared vision, team learning and system thinking). The method of research has been descriptive correlative type. The population of the study are 310 high school principals in the city of Esfahan, Iran. A sample of 90 principals was selected by stratified sampling. The instrument employed by the study was developed by the researcher and consisted of two sets of questionnaires with 41 items on Learning Organization and the other on Transformational and Transactional Leadership with 44 items. Reliability coefficient calculated by Cronbach Alpha was 0.96 for the Learning Organization questionnaire and 0.94 for Transformational Leadership And Transactional Leadership questionnaire. The sample scored high on Learning Organization indices. There was no significant difference between male and female principals in applying transactional leadership, however female principals showed significantly higher practice of transformational leadership. The results showed that there was positive relationship between transformational and transactional leadership style with indices of- learning organization. Analysis of the relationship between transactional/transformational leadership and learning organization indices showed that transformational leadership has a positive and moderate relationship with personal mastery. This study showed that female principals practice more transformational leadership than their male counterparts and transformational leadership contributes more to personal mastery in Learning Organizations.